Mapping of Latest Methods and Trends in K3 Emergency Response on Toll Roads: Literature Review - Effendi, Khairunnisa; Mega Rahmadani SIREGAR (RADINKA JOURNAL OF HEALTH SCIENCE, 2024)
As the industrial era develops around the world, the government is rapidly developing infrastructure including toll roads. The construction industry, which provides construction services, plays an important role in this development. Toll roads are dangerous workplaces and the risk of occupational injuries is high. Workplace accidents can result in property loss, death, and delays in the production process. The management of occupational safety and health (OHS) on toll roads is a major concern to prevent industrial accidents and increase productivity. The management of occupational safety and health (OHS) on toll roads is a major concern to prevent industrial accidents and increase productivity. However, in the face of OHS emergencies on toll roads,. However, in dealing with OHS emergencies on toll roads, there is a gap between expectations and the actual situation.  This research maps the latest methods and trends in Occupational Safety and Health (OHS) emergency response on toll roads through a literature review. The results show that the application of real-time monitoring technology and predictive analytics significantly improves the effectiveness of OHS emergency response. These technologies enable early detection and rapid response to incidents and help identify potential hazards and assess risks more accurately, allowing for more targeted preventive measures.